2011
DOI: 10.1002/hep.23984
|View full text |Cite
|
Sign up to set email alerts
|

Organic anion–transporting polypeptide 1b2 (Oatp1b2) is important for the hepatic uptake of unconjugated bile acids: Studies in Oatp1b2-null mice

Abstract: The organic anion–transporting polypeptide 1b family (Oatp1b2 in rodents and OATP1B1/1B3 in humans) is liver-specific and transports various chemicals into the liver. However, the role of the Oatp1b family in the hepatic uptake of bile acids (BAs) into the liver is unknown. Therefore, in Oatp1b2-null mice, the concentrations of BAs in plasma, liver, and bile were compared with wild-type (WT) mice. It was first determined that livers of the Oatp1b2-null mice were not compensated by altered expression of other h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
86
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 30 publications
12
86
0
Order By: Relevance
“…In mice engineered to delete the entire Oatp1a/ 1b locus (encompassing Slco1b2 , Slco1a4 , Slco1a1 , Slco1a6 , and Slco1a5 ), plasma levels of conjugated bile acids were unchanged, whereas unconjugated bile acid levels increased by approximately 13-fold ( 13 ). Similar results were obtained for a mouse model where only the Oatp1b2 ( Slco1b2 ) gene was deleted, indicating that this OATP is primarily responsible for mediating hepatic clearance of unconjugated bile acids in mice ( 50 ). Because unconjugated bile in male but not female mice.…”
Section: Intestinal Apical Brush Border Membrane Transportsupporting
confidence: 72%
“…In mice engineered to delete the entire Oatp1a/ 1b locus (encompassing Slco1b2 , Slco1a4 , Slco1a1 , Slco1a6 , and Slco1a5 ), plasma levels of conjugated bile acids were unchanged, whereas unconjugated bile acid levels increased by approximately 13-fold ( 13 ). Similar results were obtained for a mouse model where only the Oatp1b2 ( Slco1b2 ) gene was deleted, indicating that this OATP is primarily responsible for mediating hepatic clearance of unconjugated bile acids in mice ( 50 ). Because unconjugated bile in male but not female mice.…”
Section: Intestinal Apical Brush Border Membrane Transportsupporting
confidence: 72%
“…While the cause of the conjugated bilirubin elevation has not been determined, the increase in unconjugated bilirubin supports a role of Oatps in hepatocellular uptake of bilirubin. Mild elevation of mainly conjugated bilirubin is also observed in mice with inactivated Slco1b2 (Zaher et al, 2008), which was recently confirmed (Csanaky et al, 2011). Taken together, these human and animal data strongly support a physiological involvement of hepatocellular OATPs in the hepatic uptake of unconjugated and conjugated bilirubin.…”
Section: Bilirubinsupporting
confidence: 70%
“…We explored the possible mechanisms for altered canalicular cholesterol secretion following LD feeding using RNA profi ling of candidate transporter genes as a fi rst step in identifying the pathways involved. The fi ndings show decreased mRNA abundance of the intracellular cholesterol transporter Abcg1 ( 18 ) in Mttp-LKO and DKO mice and increased abundance of bile acid transporters Abcb11 ( 19 ) and Oatp4 ( 20 ) in DKO mice, but no changes in mRNA expression of the canalicular cholesterol effl ux transporter Abcg5/g8 or of Srb1 ( Fig. 3A ).…”
Section: Short-term Aso-mediated Hepatic Mttp Knockdown Attenuates Ldmentioning
confidence: 95%